2021
DOI: 10.3928/19404921-20210526-01
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers' Conceptions of Trust in Home Health Care Providers

Abstract: Trust is important to family caregivers of older adults receiving home health care (HHC). Caregivers rely extensively on nurses, home health aides, and other providers to manage complex care tasks. The current study examined how family caregivers conceive of trust in HHC providers. Directed content analysis methods were applied to 40 qualitative interviews conducted with caregivers of HHC patients aged ≥65 years. Results indicated that caregivers invested trust in providers who displayed competencies in caring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We created a semi‐structured interview guide (Table S1) based on study team expertise, our conceptual framework, 11 and existing literature 4,5,12,16–22 . Interviews were conducted between August and October 2020 during the second surge of the COVID‐19 pandemic, prompting inclusion of questions regarding the pandemic's effect on interactions with caregivers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We created a semi‐structured interview guide (Table S1) based on study team expertise, our conceptual framework, 11 and existing literature 4,5,12,16–22 . Interviews were conducted between August and October 2020 during the second surge of the COVID‐19 pandemic, prompting inclusion of questions regarding the pandemic's effect on interactions with caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…research identified a range of factors as impactful for caregiver participation during HHC: individual factors, including older adult care needs and caregiver experience 4,5,12,16,17 ; interpersonal factors, including rapport between caregiver and clinician [18][19][20] ; and structural factors, including HHC agency resources and staffing. 6,17,21,22 We included these three categories as domains in our framework, which helped guide our data collection and analysis by suggesting initial areas of inquiry and related content code domains.…”
Section: Why Does This Paper Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies examining the role of family caregivers during home health suggest the importance of structural factors (e.g., agency training resources, staffing), interpersonal factors (e.g., communication and trust between caregiver/clinician or caregiver/older adult), and individual factors (e.g., caregiver education level, severity of patient care needs) as meaningful determinants of caregiver interactions with the care team. 3,9,10,[19][20][21][22][23][24][25][26] Based on this existing literature and on our study team's content expertise, we developed a conceptual framework (Figure 1) to guide our study. This framework recognizes the importance of these three categories-structural, interpersonal, and individual-and posits how they may interact to affect family caregiver training during home health.…”
Section: Data Collectionmentioning
confidence: 99%
“…Agencies might do more to facilitate good matches by eliciting bidirectional feedback that allows both people with dementia and/or their family caregivers as well as paid caregivers to assess how care is working. This process would need to explicitly acknowledge that the process of building trusting relationships takes time (Reckrey, Geduldig, et al, 2019; Russell et al, 2021; Woodward et al, 2004).…”
Section: Discussionmentioning
confidence: 99%